Penampilan, Kualitas Kimia, dan Off-Odor Daging Itik (Anas plathyrynchos) yang Diberi Pakan Mengandung Beluntas (Pluchea indica L. Less) - Rukmiasih Rukmiasih; P S Hardjosworo; W G Piliang; J Hermanianto; A Apriyantono (Media Peternakan, 2010)
Duck meat is not preferred because its off-odor. Its off-odor is caused by lipid oxidation which preventable by antioxidant. Beluntas has antioxidant and anti nutrition. This research was designed to know the level of beluntas and feeding duration on performance, chemical, and duck's meat off-odor. Beluntas was given to 108 culling ducks, about 12 months old. The research used a completely randomized design with 3 x 3 factorial models, with 3 replicates. The factors were different levels of beluntas (0%, 1%, and 2%) in the ration, and feeding duration of each ration (3, 5, and 7 weeks). The data collected were analyzed using analysis of variance and Tukey's test. The results showed that no interaction was found between the two factors. Beluntas did not affect duck's performance. Feeding duration of each ration affected the fat and fatty acid content (P < 0.01) and TBARS (thiobarbituric reactive subtances) value of the meat with skin (P < 0.05). Beluntas level at 1% increased C18:0 (P < 0.05) and total (C18:2 and C18:3) (P < 0.052).  Beluntas levels at 1% and 2% reduced (P < 0.01) duck's meat off-odor and increased (P < 0.05) consumers preference. This research concluded that the inclusion of 1% beluntas for 3 weeks was effective to reduce duck's meat off-odor without negative impact on performance.